2022
DOI: 10.1111/dth.15573
|View full text |Cite
|
Sign up to set email alerts
|

Facial dermatoses and use of protective mask during Covid‐19 pandemic: A clinical and psychological evaluation in patients affected by moderate–severe atopic dermatitis under treatment with dupilumab

Abstract: During the SARS‐COV‐2 pandemic, using face masks became mandatory in many countries. Although evidence suggests that masks can exacerbate several inflammatory skin diseases, few studies focus on their real impact on eczema localized to the face in atopic dermatitis (AD) patients. The aim of this study is to evaluate facial eczema prevalence during pandemic and its psychological impact in AD patients pre‐assessed for systemic treatment and/or in therapy with dupilumab. This study includes 71 patients affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
(59 reference statements)
0
2
0
Order By: Relevance
“…Heavy metals exposure (a factor of air pollution) has similarly been associated with allergic diseases, acting as a direct activator of Th2 cells as well as an adjuvant, increasing the effect of other allergens 42 . In addition, the use of face masks has further enhanced the protective effect as studies have shown that they reduce allergic diseases, particularly AD 45 , 46 . While face masks could have an inflammatory effect on facial dermatoses due to increased skin hydration, temperature, and sebum secretion, it has been found that in patients with AD, facial eczema is deceased due to covering sensitive areas 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy metals exposure (a factor of air pollution) has similarly been associated with allergic diseases, acting as a direct activator of Th2 cells as well as an adjuvant, increasing the effect of other allergens 42 . In addition, the use of face masks has further enhanced the protective effect as studies have shown that they reduce allergic diseases, particularly AD 45 , 46 . While face masks could have an inflammatory effect on facial dermatoses due to increased skin hydration, temperature, and sebum secretion, it has been found that in patients with AD, facial eczema is deceased due to covering sensitive areas 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of face masks has further enhanced the protective effect as studies have shown that they reduce allergic diseases, particularly AD 45 , 46 . While face masks could have an inflammatory effect on facial dermatoses due to increased skin hydration, temperature, and sebum secretion, it has been found that in patients with AD, facial eczema is deceased due to covering sensitive areas 46 . In 2022, many COVID-19 regulations began to be rescinded, with South Korea removing the mask mandate and other social restrictions as the pandemic started to wind down.…”
Section: Discussionmentioning
confidence: 99%